Service Open Innovation; Design Elements for the Food and Beverage Service Business - Ki Woong Nam; Bo Young Kim; Bruce W Carnie (Journal of Open Innovation: Technology, Market and Complexity, 2018)
Despite the well-recognised contribution of design to business, practitioners still find it challenging to manage design assets. Given that one cannot manage a business without measuring these assets, researchers and practitioners deem that the lack of a practical measuring tool for design is the cause of this unfavorable situation. Hence, establishing relevant criteria for measuring design effectiveness is essential for developing the tools. However, criteria must anticipate key business outcomes in order to demonstrate effectiveness, and to propose actionable items. Whether the outcome is sales figures or customer satisfaction survey results, the criteria should clearly link with business goals. Also, the technologies in the Fourth Industrial Revolution facilitate the quantification of customer behaviour related to business performance, such as lingering time on the website for shopping. In this context, statistical understanding of design elements is critical for determining appropriate strategies in the era of digitalised data. By utilising a Service Blueprint, this study also proposes a novel approach to tackle current challenges regarding the open innovation process. Since appropriately-developed design elements are the prerequisite of successful measurement, this study extracts the elements through in-depth interviews, and examines them quantitatively with existing business theory. As a result, design elements for the food and beverage service business are confirmed by using the Structural Equation Modeling.